Understanding the sexual and reproductive health needs of immigrant adolescents in Canada: A qualitative study - Meherali, Salima; Louie-Poon, Samantha; Idrees, Sobia; Kauser, Samar; Scott, Shannon; Salami, Bukola; Valliantos, Helen; Meherali, Kainat Moez; Patel, Krishan; Suthar, Puja; Akbarzada, Zohra; Marcus, Ivan; et al. (Frontiers in Reproductive Health, 2022)
Background Literature suggests that immigrant adolescents receive limited sexual and reproductive health (SRH) education and rarely utilize SRH services in Canada. This study sought to explore the SRH information needs of immigrant adolescents in the province of Alberta. Methods A qualitative descriptive methodology was undertaken to conduct 21 individual interviews with immigrant adolescents in Alberta. Results A total of four themes emerged from the interviews: (1) Barriers to SRH; (2) needs of adolescents regarding SRH; (3) sources of knowledge; and (4) strategies to improve SRH. Our findings document the conflicting needs and preferences between adolescents and their parents regarding access to SRH resources and services. Discussion Adolescents often felt unprepared to deal with their SRH issues due to socio-cultural barriers and conflicts with their parents' conservative attitude toward SRH concerns. Structural barriers to accessing SRH resources and services were also reported, including the location and cost of services. As a result, the majority of adolescents relied on digital methods to receive SRH information. Conclusion This study highlights that future research and SRH service provider efforts need to remain cognizant of the positionality of immigrant adolescents and explore innovative ways to deliver SRH resources and services that meet their unique needs.